Raw Materials, Rearmament, and Economic Development - Mason, Edward S. (Quarterly Journal of Economics, 1952)
I. Current Materials Shortages in Relation to the Rearmament Program, 327. — II. The Long-run Materials Outlook; the Effect of Technological Change, 328. — III. Foreign Sources of Supply; Industrialization v. Increased Output of Primary Products, 332. — IV. Obstacles to the Expansion of Foreign Sources of Supply, 337. — V. Materials Security, 339. — VI. Conclusion, 340.